Heads or tails: confusion about “proximal” and “distal” terminology for pancreaticobiliary anatomy - Khara, Harshit S.; Kothari, Truptesh H.; Johal, Amitpal S.; Kothari, Shivangi T.; Ahuja, Nina; Bhanushali, Ashok; Kotru, Anil; Berger, Andrea; Kaul, Vivek; Gross, Seth A.; DiMaio, Christopher J.; Hale, William B.; Abbass, Rami; Ryou, Marvin; Sethi, Amrita; Turner, Brian G.; Fockens, Paul; Diehl, David L. (Endoscopy International Open, 2018)
Background and study aims The anatomical meaning of the terms “proximal” and “distal” in relation to the pancreaticobiliary anatomy can be confusing. We aimed to investigate practice patterns of use of the terms “proximal” and “distal” for pancreaticobiliary anatomy amongst various medical specialties. Materials and methods An online survey link to a normal pancreaticobiliary diagram was emailed to a multispecialty physician pool. Respondents were asked to label various parts of the common bile duct (CBD) and pancreatic duct (PD) using the terms “proximal,” “distal,” “not sure,” or “other.” Variability in use of these terms between specialties was assessed. Results We received 370 completed surveys from 182 gastroenterologists (49.2 %), 97 surgeons (26.2 %), 68 radiologists (18.4 %), and 23 other physicians (6.2 %). There was overall consensus in describing the upper/sub-hepatic CBD as “proximal CBD” (73.8 %, P = 0.1499) and the lower/pre-ampullary portion as “distal CBD” (84.6 %, P = 0.1821).However, there was marked variability when describing the PD. The PD in the head of the pancreas was labeled as “proximal PD” by 42.4 % and “distal PD” also by 42.4 % (P < 0.0001); and in the tail as “proximal PD” by 41.4 % and “distal PD” by 43.2 % (P < 0.0001). Only 13.8 % of respondents used descriptive terminology (“PD in the head” or “PD in the tail”) for the PD. Radiologists most often used descriptive terminology for both the CBD and PD. Surgeons most consistently called “proximal PD” in the head, and “distal PD” in the tail of the pancreas.Conclusions Although use of the terms “proximal” and “distal” is still very common to describe pancreaticobiliary anatomy, there is a discordance about its meaning, particularly for the PD. Use of descriptive terminology may be a more accurate alternative to prior ambiguous terminologies such as “proximal” or “distal” and can serve to improve communication and decrease the possibility of medical errors.